The Role of Perspective Shifts for Processing and Translating Discourse Relations. Issue 7 (2nd October 2016) - Zufferey, Sandrine; Gygax, Pascal M.
Abstract : Previous research has suggested that some discourse relations are easier to convey implicitly than others due to cognitive biases in the interpretation of discourse. In this article we argue that relations involving a perspective shift, such as confirmation relations, are difficult to convey implicitly. We assess this claim with two empirical studies involving the ambiguous French connective en effet, which can either convey a causal relation or a confirmation relation. First, we compare the processing of implicit and explicit causal and confirmation relations conveyed by this connective in a self-paced reading experiment and show that removing the connective in confirmation relations disturbs processing. Second, we compare the percentage of implicit translations of en effet for both discourse relations across three target languages using parallel directional corpora and find that causal relations always lead to more implicit translations than confirmation relations.